2020
DOI: 10.3389/fnhum.2020.00326
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Empathy in Patients With Chronic Low Back Pain: A Structural–Functional Magnetic Resonance Imaging Study

Abstract: Objective: Many pieces of research have focused on pain within individuals, but little attention has been paid to whether pain can change an individual's empathic ability and affect social relationships. The purpose of this study is to explore how chronic low back pain changes empathy. Methods: Twenty-four chronic low back pain patients and 22 healthy controls were recruited. We set up an experimental pain-exposed model for each healthy subject. All subjects received a painful-empathic magnetic resonance scan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…This study revealed the impaired cognitive empathy (i.e., lower squared cognitive empathy accuracy and longer task completion time based on the MET-C) in chronic MSK pain patients compared to HCs. This is consistent with previous research on chronic MSK pain, which found impaired empathy (as measured by the Basic Empathy Scale in Adults) in patients with chronic low back pain [ 17 ]. However, we found that the chronic MSK pain patients' emotional empathy was not impaired.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study revealed the impaired cognitive empathy (i.e., lower squared cognitive empathy accuracy and longer task completion time based on the MET-C) in chronic MSK pain patients compared to HCs. This is consistent with previous research on chronic MSK pain, which found impaired empathy (as measured by the Basic Empathy Scale in Adults) in patients with chronic low back pain [ 17 ]. However, we found that the chronic MSK pain patients' emotional empathy was not impaired.…”
Section: Discussionsupporting
confidence: 93%
“…Empathy ability predicted self-perceived social support and positive life changes, which allows resilience in response to chronic pain [ 16 ]. Additionally, a study reported that patients with chronic low back pain had impaired empathy (as measured by the Basic Empathy Scale in Adults) [ 17 ], and improving empathy ability improves interpersonal relationships and quality of life [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that patients suffering from pain also have abnormal empathic responses to the pain of others. Ma et al ( 2020 ) investigated how chronic low back pain changes empathy and the results showed that patients with the chronic low back pain displayed lower scores on the subscale scores of emotional disconnection and cognitive empathy, and the discomfort rating of watching painful stimuli. Shin et al ( 2013 ) focused on the empathic abilities differences between patients with complex regional pain syndrome (CRPS) Type I and healthy control subjects and found that patients with CRPS showed poorer performance in accuracy of identifying emotional states of others and there was a significant association between the deficit in social-emotion recognition and the affective dimension of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has also shown that CRPS patients displayed impaired cognitive and emotional empathic abilities indexed by lower scores in perspective taking and empathic concern and higher scores in personal distress of the IRI (Sohn et al, 2016 ). Studies on the neural mechanism of clinical chronic pain showed that the chronic low back pain patients displayed multiple abnormal brain pathways centered on the anterior insula (AI) (Ma et al, 2020 ) and patients with chronic pain disorder displayed lower activation of the left perigenual ACC (Noll-Hussong et al, 2013 ). AI and ACC have been considered as key areas of pain empathy (Fan et al, 2011 ; Lamm et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is the overall reflection of the physiological activity of brain nerve cells on the surface of cerebral cortex or scalp. Compared with magnetoencephalogram (MEG) [4], functional magnetic resonance imaging (FMRI) [5], positron emission tomography (PET) [6] and other research tools, EEG is still an important tool for monitoring brain activity due to its relatively low cost, convenience of recording and not easily falsified [7]. EEG has gradually been applied in the auxiliary diagnosis of a number of diseases [8][9].…”
Section: Introductionmentioning
confidence: 99%